2019
DOI: 10.1038/s41598-019-46099-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of physiological stress by urban green space in a multisensory virtual experiment

Abstract: Although stress is an increasing global health problem in cities, urban green spaces can provide health benefits. There is, however, a lack of understanding of the link between physiological mechanisms and qualities of urban green spaces. Here, we compare the effects of visual stimuli (360 degree virtual photos of an urban environment, forest, and park) to the effects of congruent olfactory stimuli (nature and city odours) and auditory stimuli (bird songs and noise) on physiological stress recovery. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
198
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(220 citation statements)
references
References 56 publications
16
198
3
3
Order By: Relevance
“…However, the results of previous VR studies are confounded by motion sickness, inadequate controls, or limited sensory inputs from the real nature treatment. Building on previous research that has demonstrated nature videos in VR generally provide beneficial effects (White et al, 2018) and that these effects are superior to those effects elicited from videos of built environments in VR (van den Berg et al, 2016;Tanja-Dijkstra et al, 2018;Hedblom et al, 2019), this is the first study to compare outdoor nature with virtual nature that has attempted to overcome these previous limitations while also adjusting for a range of individual differences related to nature and VR. We compared changes in mood, restorativeness, and physiological arousal after 6 min of exposure to outdoor nature, VR nature, and an indoor control in a sample of healthy undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the results of previous VR studies are confounded by motion sickness, inadequate controls, or limited sensory inputs from the real nature treatment. Building on previous research that has demonstrated nature videos in VR generally provide beneficial effects (White et al, 2018) and that these effects are superior to those effects elicited from videos of built environments in VR (van den Berg et al, 2016;Tanja-Dijkstra et al, 2018;Hedblom et al, 2019), this is the first study to compare outdoor nature with virtual nature that has attempted to overcome these previous limitations while also adjusting for a range of individual differences related to nature and VR. We compared changes in mood, restorativeness, and physiological arousal after 6 min of exposure to outdoor nature, VR nature, and an indoor control in a sample of healthy undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should also inform decisions about the necessary "dosages" of outdoor and virtual nature needed to elicit clinical effects. Laboratory studies could incorporate more sensory inputs than we have done, such as the smells of nature (Hedblom et al, 2019), to create more immersive and potentially restorative experiences, or overlaying complementary therapeutic modalities such as slow-paced breathing and biofeedback (Blum et al, 2019). Studies in clinical settings or densely populated areas where residents do not have safe access to nature could examine whether these potential users would benefit from VR nature.…”
Section: Opportunities For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…IVN technology might further advance the field of nature in indoor settings by generating a more immersive and life-like experience. Although there is a general lack of research regarding the effectiveness of implementing IVNs in the workplace, some research has demonstrated that IVNs can induce stress reduction in experimental trials on healthy adults [50,[58][59][60]. Moreover, exposure to IVN has been found to be a more effective tool to reduce anxiety levels and improve mood states when compared to images of nature presented on a traditional computer screen [29].…”
Section: Enable: Virtual Nature As a Supplement To Real Naturementioning
confidence: 99%
“…Celuppi et al [51], when studying the Brazilian population, approaches that pedestrians are affected by the subjective, psychological, cultural and social aspects as well as their state of mind. Thus, it is noticed that the feeling of comfort is directly linked to the experience built during their lifes [51][52][53]. Therefore, the impacts of external, environmental factors and statistical methods are often used to offset the influence of difficult to measure personal subjective internal factors [23,40].…”
Section: Introductionmentioning
confidence: 99%